Legal Analysis and Health Insurance System in Indonesia - Frans Simangunsong; Budiarsih Budiarsih (IHSA Institute, 2023)
This research was conducted to find out how the legal urgency analysis and health financing system in Indonesia are. What are the procedures and challenges of the health financing system through BPJS in Indonesia? The method used in this study is normative research, namely studying various legal regulations or laws that are appropriate, while analysis is carried out through literature reviews of various relevant journals to find new hypotheses and new recommendations. The results of this study found that the urgency of legal regulation and the financing system and health insurance is a basic right as the human rights concept ratified by Indonesia as a form of welfare state. That fulfillment of the right to health through the SJSN system and choosing BPJS as the managing institution. BPJS mechanisms already exist but there are still deficiencies in practice. The National Health Insurance implements a tiered health service system, consisting of First Level Health Facilities and Advanced Referral Level Health Facilities.